Single Nucleotide Primer Extension to Detect Genetic Diseases: Experimental Application to Hemophilia B (Factor IX) and Cystic Fibrosis Genes - Kuppuswamy, Mohan N.; Hoffman, Joseph W.; Kasper, Carol K.; Spitzer, Silvia G.; Groce, Stephanie L.; Bajaj, S. Paul (Proceedings of the National Academy of Sciences - PNAS, 1991)
In this report, we describe an approach to detect the presence of abnormal alleles in those genetic diseases in which frequency of occurrence of the same mutation is high (e.g., cystic fibrosis and sickle cell disease), and in others in which multiple mutations cause the disease and the sequence variation in an affected member of a given family is known (e.g., hemophilia B). Initially, from each subject, the DNA fragment containing the putative mutation site is amplified by the polymerase chain reaction. For each fragment two reaction mixtures are then prepared. Each contains the amplified fragment, a primer (18-mer or longer) whose sequence is identical to the coding sequence of the normal gene immediately flanking the 5' end of the mutation site, and either an α-32P-labeled nucleotide corresponding to the normal coding sequence at the mutation site or an α-32P-labeled nucleotide corresponding to the mutant sequence. Single nucleotide primer extensions are then carried out and analyzed by denaturing polyacrylamide gel electrophoresis and autoradiography. As predicted by the Watson-Crick base-pair rule, in the wild type only the normal base, in an affected member only the mutant base, and in carriers both the normal and the mutant base are incorporated into the primer. Thus, an essential feature of the present methodology is that the base immediately 3' to the template-bound primer is one of those altered in the mutant, since in this way an extension of the primer by a single base will give an extended molecule characteristic of either the mutant or the wild type. The method is rapid and should be useful in carrier detection and prenatal diagnosis of every genetic disease with a known sequence variation.